Role of CD24 Polymorphisms in the Susceptibility to Inflammatory Bowel Disease. Issue 1 (January 2014) - Lisiansky, Victoria; Kraus, Sarah; Naumov, Inna; Kazanov, Dina; Nabiochtchikov, Ilana; Toledano, Ohad; Leshno, Moshe; Avivi, Doran; Dotan, Iris; Arber, Nadir; Moshkowitz, Menachem
Background: Inflammatory bowel disease (IBD) results from an inappropriate inflammatory response in which genetic, immune, and environmental factors all play important roles. Recently, single nucleotide polymorphisms (SNPs) in the CD24 gene have been associated with the development of several autoimmune diseases. Aim: To evaluate whether CD24 SNPs, are associated with risk of ulcerative colitis (UC) and Crohn's disease (CD). Methods: The CD24 polymorphisms C170T (rs8734), TG1527del (rs3838646), A1626G (rs1058881), and A1056G (rs1058818) were assessed in a case-control study of an Israeli cohort comprising 117 IBD patients and 105 age and gender-matched healthy controls. Restriction fragment length polymorphism (RFLP) analysis was performed using BstX1, Bsr1, Mfe1, and BstU1 restriction enzymes. Odds ratios (OR) and 95% confidence intervals (CI) were estimated by logistic regression models. Results: Carriers of the C170T SNP were at increased risk of IBD (OR=3.022, 95% CI: 1.748–5.223, p=0.001), UC (OR=3.002, 95% CI: 1.661–5.427, p=0.001) and CD (OR=3.077, 95% CI: 1.334–7.095, p=0.008). Carrying the A1626G and A1056G SNPs was found to be a risk factor for IBD (OR=2.460, 95% CI: 1.420–4.259, p=0.001 and OR=1.856, 95% CI: 1.011–3.405, p=0.01), UC (OR=2.218, 95% CI: 1.207–4.075, p=0.01 and OR=1.944, 95% CI: 0.995–3.798, p=0.01) but not for CD (p=0.086 and p=0.299). The A1626G and TG1527del were found to be associated with younger age of IBD onset (p=0.022 and p=0.027, respectively). Conclusions: The CD24 C170T polymorphism is associated with IBD risk. The A1626G and A1056G SNPs might be associated only with UC risk. These findings suggest CD24 as a new genetic susceptibility factor, with clinical implications in the prediction of IBD prognosis and therapy.